Genetic resources for methane production from biomass described with the Gene Ontology - Purwantini, Endang; Torto-Alalibo, Trudy; Lomax, Jane; Setubal, João C.; Tyler, Brett M.; Mukhopadhyay, Biswarup (Frontiers in Microbiology, 2014)
Methane (CH4) is a valuable fuel, constituting 70-95% of natural gas, and a potent greenhouse gas. Release of CH4 into the atmosphere contributes to climate change. Biological CH4 production or methanogenesis is mostly performed by methanogens, a group of strictly anaerobic archaea. The direct substrates for methanogenesis are H2 plus CO2, acetate, formate, methylamines, methanol, methyl sulfides, and ethanol or a secondary alcohol plus CO2. In numerous anaerobic niches in nature, methanogenesis facilitates mineralization of complex biopolymers such as carbohydrates, lipids and proteins generated by primary producers. Thus, methanogens are critical players in the global carbon cycle. The same process is used in anaerobic treatment of municipal, industrial and agricultural wastes, reducing the biological pollutants in the wastes and generating methane. It also holds potential for commercial production of natural gas from renewable resources. This process operates in digestive systems of many animals, including cattle, and humans. In contrast, in deep-sea hydrothermal vents methanogenesis is a primary production process, allowing chemosynthesis of biomaterials from H2 plus CO2. In this report we present Gene Ontology (GO) terms that can be used to describe processes, functions and cellular components involved in methanogenic biodegradation and biosynthesis of specialized coenzymes that methanogens use. Some of these GO terms were previously available and the rest were generated in our Microbial Energy Gene Ontology (MENGO) project. A recently discovered non-canonical CH4 production process is also described. We have performed manual GO annotation of selected methanogenesis genes, based on experimental evidence, providing “gold standards” for machine annotation and automated discovery of methanogenesis genes or systems in diverse genomes. Most of the GO-related information presented in this report is available at the MENGO website (http://www.mengo.biochem.vt.edu/).